Modeling and Analysis of Vehicle Shimmy with Consideration of the Coupling Effects of Vehicle Body - Xiaogao Li; Ning Zhang; Xianjian Jin; Nan Chen (Shock and Vibration)
Based on the Lagrange equation, a 9-degrees-of-freedom shimmy model with consideration of the coupling effects between the motions of vehicle body and the shimmy of front wheels and a 5-degrees-of-freedom shimmy model ignoring these coupling effects for a vehicle with double-wishbone independent front suspensions are presented here to study the problem of vehicle shimmy. According to the eigenvalue loci of system’s Jacobian matrix plotted on the complex plane, the Hopf bifurcation characteristics of nonlinear shimmy are studied and the conditions for the generation of limit cycle are analyzed. Numerical calculation and simulation are used to study the dynamic behavior of vehicle shimmy. By comparing the dynamic responses of two different shimmy models, the coupling effects of vehicle body on vehicle shimmy are studied. Finally, the relationship between the amplitude of each DoF and vehicle velocity and the influences of vehicle parameters such as the mass of vehicle body, the longitudinal position of the center of gravity of vehicle body, and the inclination angle of front suspension on shimmy are studied.